Risk attitudes, development, and growth: Macroeconomic evidence from experiments in 30 countries - Ferdinand M. Vieider; Thorsten Chmura; Peter Martinsson (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
We measure risk attitudes in 30 different countries in a controlled, incentivized experiment (N = 3025). At the macroeconomic level, we find a strong and highly significant negative correlation between the risk tolerance of a country and income per capita. This gives rise to a paradox, seen that risk tolerance has been found to be positively associated with personal income within countries. We show that this paradox can be explained by unified growth theory. These results are consistent with the prediction that risk attitudes act as a transmission mechanism for growth by encouraging entrepreneurship. Furthermore, our study shows that risk attitudes vary considerably between countries and that for typical experimental stakes, risk seeking or neutrality is just as frequent as risk aversion.
Keywords: D01; D03; D81; E02; O10; O11; O12; 330; risk attitudes; cultural comparison; economic growth; comparative development